Contribution of Leisure Satisfaction, Acceptance Disability, and Social Relationship to Life Satisfaction among Korean Individuals with Intellectual Disability. Issue 3 (2nd July 2016) - Kim, Junhyoung; Schilling, Mary Lou; Kim, May; Han, Areum
ABSTRACT: There is a dearth of literature that explores the relationships among leisure satisfaction, acceptance of disability, social relationships, and life satisfaction among adults with intellectual disability from Eastern countries. The purpose of this study was to examine how leisure satisfaction, disability acceptance, and social relationships are associated with life satisfaction among Korean adults with mild intellectual disability. This study used the 2011 Panel Survey of Employment for the Disabled (PSED). Using hierarchical multiple regression analysis, the results showed that leisure satisfaction and disability acceptance were statistically significant predictors of life satisfaction. This study suggests that leisure satisfaction and positive disability acceptance can contribute to the psychological and physiological well-being of adults with intellectual disability.